2007
DOI: 10.1073/pnas.0702599104
|View full text |Cite
|
Sign up to set email alerts
|

Ground squirrels use an infrared signal to deter rattlesnake predation

Abstract: The evolution of communicative signals involves a major hurdle; signals need to effectively stimulate the sensory systems of their targets. Therefore, sensory specializations of target animals are important sources of selection on signal structure. Here we report the discovery of an animal signal that uses a previously unknown communicative modality, infrared radiation or ''radiant heat,'' which capitalizes on the infrared sensory capabilities of the signal's target. California ground squirrels (Spermophilus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 29 publications
0
53
1
Order By: Relevance
“…Ground squirrels increase the temperature of their tail when tail-flagging towards infrared-sensitive rattlesnakes [19]. However, we found that tail-flagging did not influence the accuracy of snake strikes, suggesting that sensory confusion is an unlikely mechanism by which tail-flagging deters snake strikes.…”
Section: Discussion (A) Strike Behaviourcontrasting
confidence: 47%
See 1 more Smart Citation
“…Ground squirrels increase the temperature of their tail when tail-flagging towards infrared-sensitive rattlesnakes [19]. However, we found that tail-flagging did not influence the accuracy of snake strikes, suggesting that sensory confusion is an unlikely mechanism by which tail-flagging deters snake strikes.…”
Section: Discussion (A) Strike Behaviourcontrasting
confidence: 47%
“…When encountering rattlesnakes, both pup (recently weaned) and adult ground squirrels approach, often within striking distance, and invariably tail-flag (wave tail side-to-side) [16 -18]. Ground squirrels increase the temperature of their tail when tail-flagging towards infrared-sensitive rattlesnakes, but not when tail-flagging towards non-infrared-sensitive gopher snakes [19]. This suggests that tail-flagging serves a specific function for communicating with snake predators.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that predator-specific alarm calls can also benefit the signaler directly (Cheney & Seyfarth, 1981). Predators often differ with regard to sensory and psychological specializations, which is likely to act as a direct selection factor in the evolution of form and patterning of alarm signals (e.g., Owings & Morton, 1997;Rundus, Owings, Joshi, Chinn, & Giannini, 2007).…”
Section: Conspecific Warningmentioning
confidence: 99%
“…In this view, the form and patterning of alarm signals are determined by the sensory bias of the predator, regardless of conspecific receivers (e.g. Marler 1965Marler , 1967Rundus et al 2007). Under this hypothesis, signals are arbitrary for conspecifics in terms of their morphology, although receivers can form associations with specific contexts, that is, they can become meaningful to them.…”
mentioning
confidence: 99%